FICI VALUE OF AQUILARIA MALACCENSIS LEAVES EXTRACT AND AMOXICILLIN AGAINST PROTEUS MIRABILIS AND PSEUDOMONAS AERUGINOSA - nobelia elok valentine; Pratiwi Apridamayanti; Rafika Sari (Kartika : Jurnal Ilmiah Farmasi, 2018)
Abstract Infection is a common disease caused by microbes. The use of antimicrobial drugs such as Amoxicillin is most widely used in Indonesia, but has develop resistance. The resistance of Amoxicillin can be overcome by combining it with Karas leaves (Aquilaria malaccensis Lam.) which has an antibacterial activity. This research was conducted to know the value of Fractional Inhibitory Concentration Index (FICI) from the combination of ethanolic Karas leaves extract (A.malaccensis Lam.) with amoxicillin in Gram-negative bacteria test, that is, Proteus mirabilis and Pseudomonas aeruginosa. This research was used disc diffusion method by Kirby Bauer. Minimum Inhibitory Concentration (MIC) result of ethanolic karas leaves extract (A.malaccensis Lam.)  in P.mirabilis and P.aeruginosa was 0.5mg/ml. MIC’s result of amoxicillin in P. mirabilis and P.aeruginosa sequentially were 0.0039 and 0.0625 mg/ml. Then, evaluation of MIC value from combination of ethanolic karas leaves extract and amoxicillin (1/4 x MIC, 1/2 x MIC, 1 x MIC, 2 x MIC and 4 x MIC) showed that the combination of ethanolic karas leaves extract with amoxicillin has characteristics of FICI value on each bacteria, P. aeruginosa: 0.5 (synergistic) and P.mirabilis: 8 (antagonist) Keyword: antibacteria, Aquilaria malaccensis, amoxicillin, FICI